Efektivitas Pemberian Air Rebusan Lidah Buaya (Aloe Vera) terhadap Kadar Gula Darah pada Pasien Diabetes Melitus Tipe II - Ariska Ariska (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to identify the right to provide aloe vera boiled water to reduce blood sugar levels in Type II Diabetes Mellitus patients at Batunyala Community Health Center, Praya Tengah District, Central Lombok Regency, NTB. The research design used in this study was a quasi experimental design pre and post with control group. The results of the dependent t test showed that the mean score of blood sugar levels before the intervention was 178.73 and the intervention intervention was 172.18 with an average decrease of 2.258. T test results Depending on the value of P (0.016) <(0.05) and tcount (2.899)> ttable (1.812). In conclusion, there were differences in blood sugar levels before and after the intervention in offering boiled tongue water. Keywords: Diabetes Mellitus Type II, Aloe Vera, Blood Sugar Levels